2016
DOI: 10.2174/1874331501610010084
|View full text |Cite
|
Sign up to set email alerts
|

Pimpinella Anisum and Illicium Verum: The Multifaceted Role of Anise Plants

Abstract: The role of dietary active compounds in human nutrition is an important area of investigation in the field of nutritional science. In this perspective, functional foods play a relevant role, offering a new kind of health tool that promises specific effects related to particular food components. Anise plant has a long cultural tradition in various countries all over the world, both as food and as drug. The essential oil of anise, extracted from the dry ripe fruits ofIllicium verumandPimpinella anisum, contains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Prajapati et al, (2007) and Fritz et al (2008) reported that fruits are picked before they ripe and dried, and seeds are shiny brown or reddish with high oil content. Vecchio et al (2016) also noted that flowers bloom from March to May, and the fruits ripe from September to October. Anethole of star anise has been utilized in folk medicine industry because of its soothing and antispasmodic properties (Ludlow et al, 2004).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Prajapati et al, (2007) and Fritz et al (2008) reported that fruits are picked before they ripe and dried, and seeds are shiny brown or reddish with high oil content. Vecchio et al (2016) also noted that flowers bloom from March to May, and the fruits ripe from September to October. Anethole of star anise has been utilized in folk medicine industry because of its soothing and antispasmodic properties (Ludlow et al, 2004).…”
Section: Introductionmentioning
confidence: 93%
“…Yadav and Bhatnagar (2007) indicate that the treatment with star anise rescues the tumor burden, lowers oxidative stress and increases the level of phase II enzymes, which may contribute to its anticarcinogenic. Both the essential oil from Chinese star anise fruit and trans-anethole are major constituents and exhibit potent inhibitory effect against all test fungi indicating that most of the observed anti-fungal properties was due to the presence of trans-anethole in the oil, which could be developed as natural fungicides for plant disease control in fruit and vegetable preservation (Huang et al, 2010;Vecchio et al, 2016).…”
Section: Modern Medicinal Usage Of Star Anisementioning
confidence: 99%
See 2 more Smart Citations
“…(I.verum) belonging to family Illiaceae, is an aromatic evergreen tree that bears a purple-red flower and a star-shaped fruit, commonly known as star anise, often used as a spice in the tropical and subtropical world [14]. I. verum has potent antimicrobial, stimulant, antiviral, anticancer, anti-oxidative, rheumatism, otalgia, antiseptic and diuretic properties [15]. However, the exact constituent responsible for the anti-QS and antibiofilm activities in I.verum remains ambiguous.…”
Section: Introductionmentioning
confidence: 99%